Protective Effect of Lactobacillus diolivorans 1Z, Isolated From Brazilian Kefir, Against Salmonella enterica Serovar Typhimurium in Experimental Murine Models - Abatemarco Júnior, Mario; Sandes, Sávio Henrique Cicco; Ricci, Mayra Fernanda; Arantes, Rosa Maria Esteves; Nunes, Álvaro Cantini; Nicoli, Jacques Robert; Neumann, Elisabeth (Frontiers in Microbiology, 2018)
Kefir is a beverage obtained by fermentation of milk or sugar solution by lactic acid bacteria and yeasts, and several health benefits have been attributed to its ingestion, part of them being attributed to Lactobacillus species. The objective of the present study was to evaluate, in vivo, the probiotic potential of Lactobacillus diolivorans 1Z, isolated from Brazilian kefir grains. Initially, conventional mice were orally treated daily or not during 10 days with a suspension of L. diolivorans 1Z, and then orally challenged with Salmonella enterica serovar Typhimurium. Treatment with L. diolivorans 1Z resulted in higher survival (70%) of animals after the challenge with the pathogen than for not treated mice (0%). When germ-free mice were monoassociated (PS group) or not (CS group) with L. diolivorans 1Z and challenged after seven days with S. Typhimurium, Salmonella faecal counts were significantly lower (P < 0.05) for the PS group when compared to the CS group. Histopathological analysis revealed less damage to the ileum mucosa, as demonstrated by smallest perimeter of major lesions for mice of the PS group in comparison to the group CS (P < 0.05). These findings were accompanied by a lower expression of IFN-γ and TNF-α in the intestinal tissue of PS mice. Additionally, translocation of S. Typhimurium to liver was significantly lower in PS than in CS mice (P < 0.05), and IgA levels in intestinal content and number of Küpffer cells in liver were higher. No difference was observed for hepatic cellularity between PS and CS groups (p > 0.05), but the pattern of inflammatory cells present in the liver was predominantly of polymorphonuclear in CS group and of mononuclear in the PS group, and a higher hepatic expression of IL-10 and TGF-β was observed in PS group. Concluding, L. diolivorans 1Z showed to be a potential probiotic strain that protected mice from death after challenge with S. Typhimurium, apparently by immunological modulation.